Why Are Dithienylethene‐Linked Biscobaltocenes so Hard to Photoswitch?. Issue 6 (13th March 2017) - Escribano, Alejandra; Steenbock, Torben; Stork, Conrad; Herrmann, Carmen; Heck, Jürgen
Abstract: The front cover artwork was designed by Torben Steenbock in collaboration with Carmen Herrmann and Jürgen Heck. It shows an underground railway map symbolizing the great variety of excited‐state pathways upon photoexcitation, of which only one leads to the desired target. Read the full text of the article at10.1002/cphc.201601146 . Abstract : "Attaching an organometallic unit to a dithienylethene (DTE) molecular switch can allow one to vary its switching and spectroscopic properties, and to create switchable magnetic properties. In this work, two different dithienylethene molecular switches are used as a bridge between two cobalt sandwich units…" This and more about the story behind the front cover can be found in the Full Paper at10.1002/cphc.201601146 .